The role of size in risk-taking behaviour of the banking sector: cross-country evidence - Yang, En Lin (2020)
The risk appetite plays a critical role in banking business. For the bank, it cannot avoid taking risk as leveraging risk can bring profits to bank itself. However, the financial crisis in 2007 damaged the financial system seriously, it is because of the over risk-taking behaviour in financial institutions, especially in the large banks. This paper investigate the bank risk-taking behaviour, and it also examine the relationship between influence factors such as bank size and bank risk appetite. The research bases on an international bank sample with a period from 2006 to 2017, and the fixed effects model will be used. Overall, the empirical results indicate that large size bank does not reduce the bank risk-taking, and other factors such as capital adequacy ratio also would increase the level of bank risk appetite. Besides, the too-big-to-fail bank could reduce bank risk-taking as it has insurances from the too-big-to-fail policy which is set by governments. In addition, this research separates the period from 2006 to 2017 to the period during financial crisis (2006-2008) and post-crisis period (2009-2017) to tell the different influence results between these two certain period and also 2006 to 2017.